Pharmacologically targeting molecular motor promotes mitochondrial fission for anti-cancer - Yi Qian; Meimei Zhao; Qinghua Han; Jingkang Wang; Lixi Liao; Heng Yang; Dan Liu; Pengfei Tu; Hong Liang; Kewu Zeng (Elsevier, 2021)
Mitochondrial shape rapidly changes by dynamic balance of fusion and fission to adjust to constantly changing energy demands of cancer cells. Mitochondrial dynamics balance is exactly regulated by molecular motor consisted of myosin and actin cytoskeleton proteins. Thus, targeting myosin-actin molecular motor is considered as a promising strategy for anti-cancer. In this study, we performed a proof-of-concept study with a natural-derived small-molecule J13 to test the feasibility of anti-cancer therapeutics via pharmacologically targeting molecular motor. Here, we found J13 could directly target myosin-9 (MYH9)-actin molecular motor to promote mitochondrial fission progression, and markedly inhibited cancer cells survival, proliferation and migration. Mechanism study revealed that J13 impaired MYH9-actin interaction to inactivate molecular motor, and caused a cytoskeleton-dependent mitochondrial dynamics imbalance. Moreover, stable isotope labeling with amino acids in cell culture (SILAC) technology-coupled with pulldown analysis identified HSPA9 as a crucial adaptor protein connecting MYH9-actin molecular motor to mitochondrial fission. Taken together, we reported the first natural small-molecule directly targeting MYH9-actin molecular motor for anti-cancer translational research. Besides, our study also proved the conceptual practicability of pharmacologically disrupting mitochondrial fission/fusion dynamics in human cancer therapy.